Psychosocial well-being index and sick leave in the workplace: a structural equation modeling of Wittyfit data - Colin-Chevalier, Rémi; Pereira, Bruno; Dewavrin, Samuel; Cornet, Thomas; Baker, Julien Steven; Dutheil, Frédéric (Frontiers in Psychology, 2025)
BackgroundPsychosocial well-being, which assesses emotional, psychological, social, and collective well-being, could help measure risk and duration of sick leave in workers.ObjectiveThis study aims to build a structural equation model of a psychosocial well-being index based on 10 psychosocial factors and investigate its association with sick leave.MethodsData of workers using Wittyfit was collected in 2018. Psychosocial factors (job satisfaction, atmosphere, recognition, work-life balance, meaning, work organization, values, workload, autonomy, and stress) were self-assessed using health-related surveys, while sick leave records were provided by volunteer companies.ResultsA total of 1,399 workers were included in the study (mean age: 39.4 ± 9.4, mean seniority: 9.2 ± 7.7, 49.8% of women, 12.0% managers). The prevalence of absenteeism was 34.5%, with an average of 8.48 ± 28.7 days of sick leave per worker. Structural equation modeling facilitated computation of workers’ psychosocial well-being index (AIC: 123,016.2, BIC: 123,231.2, RMSEA: 0.03). All factors, except workload (p = 0.9), were influential, with meaning (β = 0.72, 95% CI 0.69–0.74), values (0.69, 0.67–0.70) and job satisfaction (0.64, 0.61–0.66) being the main drivers (p < 0.001). Overall, psychosocial well-being was found to be a protective factor for sick leave, with a 2% decreased risk (OR = 0.98, 95% CI 0.98–0.99, p < 0.001) and duration (IRR = 0.98, 95% CI 0.97–0.99, p < 0.001) per psychosocial well-being index point.ConclusionThe psychosocial well-being index provides a measure of psychosocial well-being and helps predict sick leave in the workplace. This new indicator could be used to analyze the association between psychosocial well-being and other health outcomes.Clinical trial registrationClinicaltrials.gov, identifier NCT02596737.